Family, community, and higher education - Jenkins, Toby S. 1975- (Routledge research in education ;, 2013)
"This book explores social topics and experiences that illustrate the various ways in which the family unit influences and impacts college students. In the text, the authors not only explore family memories, but also challenge the traditional lack of inclusion and appreciation for family as knowledge producers and educational allies. This book spotlights the family unit as a critical factor within the educational experience, one that prepares, supports, and sustains educational achievement through both everyday simple lessons and critical and difficult family challenges. Through these experiences, families teach the lessons of survival that often help students to persist in college"--